Pyogenic liver abscess: case report - Lins, Adolpho Fontes (2023)
Pyogenic liver abscess is caused by the development of intrahepatic pus secondary to a local inflammatory reaction due to a bacterial infection. This is a serious condition associated with increased morbidity and mortality in those affected. Therefore, the present case report aims to: describe a severe presentation of liver abscess in the elderly, showing the intercurrences during the hospitalization period and how the patient was managed. As well as reviewing the literature on differences in etiopathogenesis and the bases of diagnosis and treatment. The elderly person in the reported case had abdominal pain, fever, anorexia and weight loss, demonstrating a subacute episode. The therapy was carried out taking into account the probable etiology and combined with complementary laboratory and imaging tests, mainly computed tomography. Antibiotic therapy and image-guided percutaneous drainage proved to be one of the mainstays of treatment